2014
DOI: 10.1016/j.exer.2014.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Recharging mitochondrial batteries in old eyes. Near infra-red increases ATP

Abstract: Progressive accumulation of age related mitochondrial DNA mutations reduce ATP production and increase reactive oxygen species output, leading to oxidative stress, inflammation and degradation. The pace of this is linked to metabolic demand. The retina has the greatest metabolic demand and mitochondrial density in the body and displays progressive age related inflammation and marked cell loss. Near infra-red (670 nm) is thought to be absorbed by cytochrome c oxidase (COX), a key element in mitochondrial respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 26 publications
6
83
1
1
Order By: Relevance
“…2013; Gkotsi et al. 2014). It is the combination of anatomical changes coincident with functional improvements that is most promising for PBM as a novel treatment for dry AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Gkotsi et al. 2014). It is the combination of anatomical changes coincident with functional improvements that is most promising for PBM as a novel treatment for dry AMD.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Gkotsi et al. 2014). Photobiomodulation (PBM) can increase mitochondrial ATP, replication, density and activity and increase RNA and protein synthesis (Passarella & Karu 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have found that following similar 670 nm light exposures, there were significant improvements in retinal mitochondrial membrane potentials and ATP production, and also reduced retinal inflammation. These were established within 3–5 days of light exposure (Kokkinopoulos et al., 2013, Gkotsi et al., 2014). Our data also showed a significant increase in retinal [HbT] although not in [HbDiff].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, absorbance of one of these wavelengths, 670 nm light, in the retina of aged animals has been shown to improve mitochondrial respiration, increasing their membrane potentials and improve ATP production (Kokkinopoulos et al., 2013, Gkotsi et al., 2014, Calaza et al., 2015). This in turn is associated with reduced retinal inflammation both in normal mice and those that are murine models of age related macular degeneration where inflammation appears early and is relatively aggressive (Kokkinopoulos et al., 2013, Begum et al., 2013, Catchpole et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…19,21,22 This photodissociation would allow oxygen fixation and thereby enhance cellular respiration and metabolism. This type of treatment has been shown to reduce production of factors associated with oxidative stress in various cell types in vitro as well as in affected tissues of laboratory animals with experimentally induced ischemiareperfusion injury or age-related retinal changes 21,[23][24][25][26] and to protect against oxidative stress by activating scavenging superoxide anions. 27 In rats with blunt-impact muscle trauma, photobiomodulation therapy blocked reactive oxygen species release and activation of nuclear factor-kB, inhibited overexpression of inducible nitric oxide synthase, reduced the inflammatory response, and decreased collagen production in the traumatized muscle, compared with traumatized muscles from rats that did not undergo photobiomodulation therapy.…”
Section: Ivddmentioning
confidence: 99%